Involvement of Insulin Like Growth Factor-I Gene Polymorphism with Diabetes and Diabetic Nephropathy in Individuals with Type 2 Diabetes in Babylon Province - Maytham Ahmed Abdul Aemah; Moaed Emran Al-Gazally; Ali Jasim Al-Sultani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Concerning type 2 diabetes mellitus (T2DM), diabetic nephropathy (DN) is a chiefmicrovascular complication.Preceding studies have proposed that insulin-like growth factor-1(IGF-1) signaling might do a significantrole in DN. The existing study was implemented to explorethe allianceof single nucleotide polymorphism(SNP) rs6214 of the IGF-1gene with T2DM and DN. The study consists of three groups, the first oneincludes50 subjects, those were apparently healthy were considered as controls. The second oneinvolves 69 patientswith T2DM without nephropathy and the third oneencompasses 89 patients who suffer from T2DM withDN. The analysis of results elucidated that thegenotype CT was decided to significantly increase the hazardof T2DM by about 2 folds and the genotype TT was established to significantly increase the risk of DN byabout 3 folds with respect to those of the genotype CC. This study concludes that theSNPrs6214 of theIGF-1gene associated with T2DM and DN.